Rezidivrisiko durch hormonale Kontrazeptiva bei Brustkrebsüberlebenden überprüft (Deutsche Zeitschrift für Onkologie, 2021)
Ostroot MK et al. Breast cancer recurrence risk after hormonal contraceptive use in survivors of reproductive age. Eur J Obstet Gynecol Reprod Biol 2021; 258: 174–178. doi: 10.1016/j.ejogrb.2020.12.035